Public Perception vs. Practice: Tracing Muslim Women's (Dis)Inheritance in Punjab, 1526-Present - Shahzad, Fiza. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of History.; Advisor: Ayesha Jalal.; Committee: Brian Hatcher, and Khaled Fahmy.; Keywords: History, Gender studies, and Islamic studies.